(untitled) - Yamasaki, Munenao (Tokyo, 1927)
Contents: General principles of exchange; money; Banks and banking; Insurance; money market, stock exchange, and state finance.
Keywords: Banks and banking,Tài chính,Ngân hàng và hoạt động ngân hàng,Finance